Facing the Challenges of Online Learning: Pedagogic Competence of Lecturers in Religious Colleges - Sukri, Urbanus (Journal of Social Science and Education Research, 2025)
The rapid shift to online learning due to the COVID-19 pandemic has significantly impacted higher education, including religious-based universities. This study examines the pedagogical competencies of lecturers in religious higher education institutions in adapting to online learning challenges. Using a qualitative research approach with a literature study method (library research), this paper analyzes various academic sources to understand the essential pedagogical skills required for effective online teaching. The findings highlight that lecturers must possess competencies in digital pedagogy, student engagement, instructional design, and technological adaptation. Furthermore, the study reveals that religious higher education institutions face unique challenges, such as integrating religious values into digital learning environments while maintaining interactivity and student-centered teaching approaches. The results emphasize the need for continuous professional development programs that enhance lecturers’ digital literacy and pedagogical strategies. Additionally, institutional support and infrastructure improvements are crucial to overcoming barriers to effective online learning. This research contributes to the ongoing discourse on online education by providing insights into the specific challenges faced by religious higher education institutions and offering recommendations for strengthening lecturers' competencies in digital pedagogy. The study concludes that developing adaptive and technology-integrated teaching strategies is essential for ensuring the quality of online learning in religious higher education institutions.